A New Approach to Transdermal Drug Delivery Using Transfersomes-Based Nanoencapsulation: A Research Update - Rajkumar, J; Sree Lakshmi, R. K.; Vineesha, Shalini (Asian Journal of Pharmaceutical Research and Development, 2022)
A primary goal of these delivery systems was to provide patients with greater convenience. This drug delivery technology is a specially constructed artificial vesicle that resembles cell vesicles and is appropriate for controlling and potentially targeted medication administration. Because they are formed of natural phospholipids, like liposomes, they are biodegradable and biocompatible. They are made up of phospholipids such as Phosphatidyl choline, edge activators such as sodium cholate, and a little amount of ethanol. Transferosome drug delivery works via two processes. For starters, as drug vectors, they remain intact after penetrating the skin. Second, they operate as penetration enhancers, breaking the stratum corneum's highly structured intercellular lipids. Based on data that it is effective without causing skin irritation, this medication delivery technique is preferred for the treatment of skin cancer. This review gives an important overview of transfersomes as drug delivery vesicles' properties, composition, manufacturing processes, formulation examples, characterization, succinct assessments of published publications and applications, and so on.